1973
DOI: 10.1192/bjp.123.1.73
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Versus Bilateral Ect in Schizophrenia

Abstract: Electroconvulsive therapy with unilateral electrode placement has been tried most often in depressive disorders (Abrams and de Vito, 1969; Cannicott, 1962; Cannicott and Waggoner, 1967; Costello et al., 1970; d'Elia, 1970; Fleminger et al., 1970; Levy, 1968; Martin et al., 1965; Strain et al., 1968; Valentine et al., 1968; Zinkin and Birtchnell, 1968; Lancaster et al., 1958), although Lancaster (op. cit.) noted that it was as effective as bilateral ECT in relieving certain other psychotic symptoms, such as cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1976
1976
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Ottosson (14) has concluded that the antidepressant effect is seizure-related and has a different neural substrate from the associated memory disturbance, and d'Elia (6) and Sand-Stromgren (15) have confirmed that unilateral non-dominant ECT has the same antidepressant effect as bilateral ECT; Doongaji et al . (7) state that both forms of treatment are equally effective in schizophrenia.…”
mentioning
confidence: 99%
“…Ottosson (14) has concluded that the antidepressant effect is seizure-related and has a different neural substrate from the associated memory disturbance, and d'Elia (6) and Sand-Stromgren (15) have confirmed that unilateral non-dominant ECT has the same antidepressant effect as bilateral ECT; Doongaji et al . (7) state that both forms of treatment are equally effective in schizophrenia.…”
mentioning
confidence: 99%
“…Efficacy The UK ECT Group 51 found that the standardised effect size between the two electrode placements was 0.03 (95% CI -0.91 to 1.03), with a mean change in efficacy score of 0.32 (95% CI -10.56 to 11.99), indicating no difference between the two electrode placements. The Cochrane Schizophrenia Group ECT review 50 found neither unilateral nor bilateral ECT to be superior in terms of global improvement (two RCTs, 184,191 RR = 0.79, not improved at end of course of ECT, 95% CI 0.5 to 1.4, n = 78). They report that none of the three trials reported long-term efficacy data.…”
Section: Unilateral Versus Bilateral Ectmentioning
confidence: 99%
“…The UK ECT Group 51 included two trials 191,192 containing 147 patients. Adolescents were included in one trial 191 and unmodified ECT was used in the other. 192 Neuroleptic medication was not coadministered in either of these studies.…”
Section: Unilateral Versus Bilateral Ectmentioning
confidence: 99%
“…Doongaji et al (1973) randomized 54 right‐handed patients with schizophrenia to a minimum of six BL, RUL, or LUL ECT. It must be noted that, unlike in the rest of the literature reviewed here, ECT was administered completely ‘unmodified’, that is, with no anesthesia or preanesthetic medication.…”
Section: Literature Reviewmentioning
confidence: 99%